Analisis Efektivitas Perputaran Piutang Pada Pembiayaan Di PT. BFI Finance Indonesia Tbk - Chichi Pratiwi; Goso Goso; Muh Halim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effectiveness of the receivables turnover rate as measured by using the receivables turnover ratio (Receivable Turnover Ratio), the average age of receivables (Avverange Collection Period/ACP), the ratio of billing and arrears ratio. The secondary data used is the financial statements of PT.BFI Finance Indonesia Tbk for 2018-2022. The data analysis technique uses simple linear regression with the help of SPSS Statistics 25. The results show that the level of accounts receivable turnover has a significant effect on the effectiveness of PT. BFI Finance Indonesia Tbk. Judging from the turnover for 4 years has increased so that the company can run effectively and efficiently in reducing to a minimum the amount of outstanding receivables. The company is improving the management of accounts receivable collection so that the percentage of billing can continue to increase and reduce the number of outstanding receivables to prevent the risk of loss of receivables. So this shows that the actions taken by the company against late payments have been managed properly. Keywords: Receivables, Effectiveness, Control, Rotation